1997
DOI: 10.1111/j.1600-0838.1997.tb00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal epidural lipomatosis. Case report and review of the literature

Abstract: Spinal epidural lipomatosis (SEL) is a condition in which excess adipose tissue is deposited circumferentially about the spinal cord in the epidural space. It is most frequently seen in patients on chronic glucocorticosteroid therapy for a variety of medical problems. This is a case report of lumbar epidural lipomatosis in a bodybuilder with radiculopathy supposedly induced by anabolic steroid intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…The clinical presentation of lumbosacral SEL may include progressive pain, weakness, numbness, incontinence, abnormal reflexes, and paralysis [32]. In a comprehensive review of all of the cases of SEL reported in the English language literature up to 2008, which included 111 cases, Al-Khawaja et al reported that thoracic SEL presented with myelopathy (55%) or paraplegia (19%) where as lumbosacral SEL presented with low back and radicular pain (54%), claudication (21%), or leg weakness (25%) [8].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of lumbosacral SEL may include progressive pain, weakness, numbness, incontinence, abnormal reflexes, and paralysis [32]. In a comprehensive review of all of the cases of SEL reported in the English language literature up to 2008, which included 111 cases, Al-Khawaja et al reported that thoracic SEL presented with myelopathy (55%) or paraplegia (19%) where as lumbosacral SEL presented with low back and radicular pain (54%), claudication (21%), or leg weakness (25%) [8].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Other cases of corticosteroid-associated SEL are related to multiple epidural steroid injections 7,8 and administration of anabolic steroids. 9 SEL has been reported in medical conditions that affect fat metabolism such as hypothyroidism 10 and protease inhibitor use in the treatment of HIV. 11,12 SEL has also been reported in Paget disease of the bone 13 and hyperprolactinemia.…”
Section: Discussionmentioning
confidence: 99%
“…In the 17 surgical patients with available data, the time course of patients' neurological deterioration was noted in days [6][7][8]10,11,13,14,17,18,20,23,24,[26][27][28][29][30][32][33][34]36,37]. The duration of symptoms refers to the period of time between when the patient first reported noticing symptoms and their definitive surgery.…”
Section: Acuity Of Symptom Onsetmentioning
confidence: 98%